The impact of relationship marketing practices on companies' market and financial performance in emerging markets - Vera Rebiazina; Elena Sharko; Svetlana Berezka (Journal of Economics, Finance and Administrative Science, 2024)
Purpose - The paper aims to reveal the impact of relationship marketing (RM) practices adopted by companies in emerging markets on their market and financial performance (FP) over a long-term, 13-year perspective. Design/methodology/approach The research design combines primary empirical data from 229 Russian companies, based on the Contemporary Marketing Practices (CMP) survey, and objective FP data from official statistical databases for 2008-2020 to verify the impact of RM practices on market and FP in the long term. Findings The research underlines the significant impact of RM practices. It is important to notice that the effect of product development (PD) on marketing performance is mediated by competitor orientation. PD affects market and FP, whose roles vary with the return on assets (ROA). Research limitations/implications Research design supplements the subjective survey data with the objective FP data on the ROA to avoid common method bias. Practical implications Implementation of RM practices by Russian companies can increase their effectiveness of performance in the long term. Originality/value This research shows the positive impact of RM practices on the FP of Russian firms over the past 13 years.
Keywords: L25; M31; 330; Emerging markets; Financial performance; Market performance; Marketing practices; Relationship marketing